Corrigendum: Spatial analysis of demersal food webs through integration of eDNA metabarcoding with fishing activities - Davide Cicala; Giulia Maiello; Fabio Fiorentino; Germana Garofalo; Daniela Massi; Alice Sbrana; Stefano Mariani; Simone D’Alessandro; Matteo Stefani; Lucie Perrodin; Tommaso Russo (Frontiers in Marine Science, 2024)

Spatial analysis of demersal food webs through integration of eDNA metabarcoding with fishing activities - Davide Cicala; Giulia Maiello; Fabio Fiorentino; Germana Garofalo; Daniela Massi; Alice Sbrana; Stefano Mariani; Simone D’Alessandro; Matteo Stefani; Lucie Perrodin; Tommaso Russo (Frontiers in Marine Science, 2024)
The evaluation of the status of marine communities, and especially the monitoring of those heavily exploited by fisheries, is a key, challenging task in marine sciences. Fishing activities are a major source of disruption to marine food webs, both directly, by selectively removing components at specific trophic levels (TL), and indirectly, by altering habitats and production cycles. Food web analysis can be very useful in the context of an Ecosystem Approach to Fisheries, but food web reconstructions demand large and expensive data sets, which are typically available only for a small fraction of marine ecosystems. Recently, new technologies have been developed to easily, quickly and cost-effectively collect environmental DNA (eDNA) during fishing activities. By generating large, multi-marker metabarcoding data from eDNA samples obtained from commercial trawlers, it is possible to produce exhaustive taxonomic inventories for the exploited ecosystems, which are suitable for food-web reconstructions. Here, we integrate and re-analyse the data of a recent study in which the α diversity was investigated using the eDNA opportunistically collected during fishing operations. Indeed, we collect highly resolved information on species feeding relationships to reconstruct the food webs at different sites in the Strait of Sicily (Mediterranean Sea) from eDNA and catch data. After observing that the trophic networks obtained from eDNA metabarcoding data are more consistent with the available knowledge, a set of food web indicators (species richness, number of links, direct connectance and generality) is computed and analysed to unravel differences in food webs structure through different areas (spatial variations). Species richness, number of links and generality (positively) and direct connectance (negatively) are correlated with increasing distance from the coast and fishing effort intensity. The combined effects of environmental gradients and fishing effort on food web structure at different study sites are then examined and modelled. Taken together, these findings indicate the suitability of eDNA metabarcoding to assist and food web analysis, obtain several food web-related ecological indicators, and tease out the effect of fishing intensity from the environmental gradients of marine ecosystems.

Numerical analysis of a one-dimensional nonlinear wave scattering at a contact interface with damageable adhesion and unilateral contact - A. Meziane; P. Blanloeuil; D. Nouira; L. Baillet; F. Massi (Wave Motion, 2023)

Novel implementation of the INFN-CHNet X-ray fluorescence scanner for the study of ancient photographs, archaeological pottery, and rock art - F. Taccetti; L. Castelli; C. Czelusniak; F. Giambi; M. Manetti; M. Massi; A. Mazzinghi; C. Ruberto; F. Arneodo; R. Torres; F. Castellá; L. Gheco; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Discard composition associated with the deep water rose shrimp fisheries (Parapenaeus longirostris, Lucas 1846) in the south-central Mediterranean Sea - G. MILISENDA; S. VITALE; D. MASSI; M. ENEA; V. GANCITANO; G. B. GIUSTO; C. BADALUCCO; M. GRISTINA; G. GAROFALO; F. FIORENTINO (Mediterranean Marine Science, 2017)
Discarding in fisheries is believed to be a waste of natural resources, as it is the part of the total catch brought on board but then returned to the sea dead or alive for any reason. This study aims to advance knowledge of the discards associated with the deep water rose shrimp fisheries in the south-central Mediterranean Sea. We address this issue by examining the data collected within the module of commercial catch monitoring (Campbiol) of European data collection framework (DCF) between January 2009 and December 2013. Multivariate data analysis and the generalized additive model (GAMs) were used to assess the spatio-temporal composition of the discard and factors influencing its distribution. Overall, discard represented 32.9±15.4% of the total catch. Multiple analysis of variance highlighted the significant effect on discard assemblage only for the factor of depth (p-value

New Mediterranean Biodiversity Records (March 2016) - P. K. KARACHLE; A. ANGELIDIS; G. APOSTOLOPOULOS; D. AYAS; M. BALLESTEROS; C. BONNICI; M. M. BRODERSEN; L. CASTRIOTA; N. CHALARI; J. M. COTTALORDA; F. CROCETTA; A. DEIDUN; et al. (Mediterranean Marine Science, 2016)
In this Collective Article on “New Mediterranean Biodiversity Records”, we present additional records of species found in the Mediterranean Sea. These records refer to eight different countries throughout the northern part of the basin, and include 28 species, belonging to five phyla. The findings per country include the following species: Spain: Callinectes sapidus and Chelidonura fulvipunctata; Monaco: Aplysia dactylomela; Italy: Charybdis (Charybdis) feriata, Carcharodon carcharias, Seriola fasciata, and Siganus rivulatus; Malta: Pomacanthus asfur; Croatia: Lagocephalus sceleratus and Pomadasys incisus; Montenegro: Lagocephalus sceleratus; Greece: Amathia (Zoobotryon) verticillata, Atys cf. macandrewii, Cerithium scabridum, Chama pacifica, Dendostrea cf. folium, Ergalatax junionae, Septifer cumingii, Syphonota geographica, Syrnola fasciata, Oxyurichthys petersi, Scarus ghobban, Scorpaena maderensis, Solea aegyptiaca and Upeneus pori; Turkey: Lobotes surinamensis, Ruvettus pretiosus and Ophiocten abyssicolum. In the current article, the presence of Taractes rubescens (Jordan & Evermann, 1887) is recorded for the first time in the Mediterranean from Italy. The great contribution of citizen scientists in monitoring biodiversity records is reflected herein, as 10% of the authors are citizen scientists, and contributed 37.5% of the new findings.

Pharmacological characterization of the nociceptin receptor mediating hyperphagia: identification of a selective antagonist - C. Polidori; G. Calo'; R. Ciccocioppo; R. Guerrini; D. Regoli; M. Massi (Psychopharmacology, 2000)